Effectiveness of Motion Visualization Through Immersive Video in Patients With Hemophilic Arthropathy Of The Ankle - Ucero-Lozano, Roberto; Pérez-Llanes, Raúl; López-Pina, Jose-Antonio; Cuesta-Barriuso, Rubén (Archives of physical medicine and rehabilitation, 2022)
To investigate the efficacy of a 180° immersive motion visualization intervention in patients with hemophilic ankle arthropathy. Multicenter cohort study. The study was conducted in three regional Hemophilia Patient Associations. 15 volunteer patients with hemophilia were recruited, mean age: 42.73 (standard deviation: 12.36) years. All patients had a diagnosis of hemophilia A or B, bilateral ankle arthropathy, and were older than 18 years. Patients with central neurological or visual problems were excluded. No patient suffered adverse effects, and all completed the study and follow-up period. A home intervention was carried out for 28 consecutive days by visualizing ankle flexion-extension movement with 180° immersive video. The duration of each session was 15 minutes. The subjects used their own smartphone coupled to VR glasses, using a mobile application designed ad hoc for the study (HEMirror®). The subjects had to remain seated in a chair with their knees flexed and their feet resting on the floor only on the heel. The primary study outcome measurements were joint health (Hemophilia Joint Health Score), range of motion (goniometry) and perceived pain intensity (Visual Analogue Scale). After the intervention there was improvement (p < 0.05) in joint health (Means difference [MD]: 1.20; 95% confidence interval [95%IC]: 0.89–1.50; Effect size [ES]: 0.48), range of motion (MD: 1.19; 95%IC: 0.80-1.58; ES: 0.53) and perceived pain intensity (MD: -3.27; 95%IC: -4.76- -1.77; ES: 0.20). Immersive video motion visualization is safe in hemophilia patients. This intervention can improve joint health, perceived pain intensity and joint range in patients with hemophilic ankle arthropathy. The authors certify that there are no conflicts of interest with any financial organization regarding the material discussed in the manuscript.